Al-Ghazali's Eco-Sufism for Environmental Preservation: Living Sufism at Pesantren Al-Anwar 3 of Central Java - Khikamuddin, M; Ainiyah, Mahfudhoh; Anwar, Moh. Kamil (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
Natural destruction is a severe problem faced by human beings up to the present. Many factors are identified, including less awareness of its preservation, no matter how much research is exposed. This study investigates how Al-Ghazali’s ecosufism theory is implemented at Pesantren Al-Anwar 3 of Central Java. This study employs a qualitative method with field research, which involves an anthropological approach to observe and analyze the implementation of al-Ghazali’s ecosufism concept regarding environmental ethics and waste management at Pesantren Al-Anwar 3 in Central Java. The research findings reveal al-Ghazali’s concept in dealing with environmental issues, including shukr (thankfulness), zuhd (asceticism), ‘uzla (seclusion) and maḥabba (love). They are practiced by Pesantren Al-Anwar 3 by creating innovative waste management systems, such as burning without emitting smoke, optimizing organic waste as worm feed, and utilizing the remaining combustion as material for paving. This shows how Al-Ghazali’s ecosufism theory is implemented in waste management and can effectively reduce the impact of natural damage.Contribution: This research contributes to overcoming natural damage by applying al-Ghazali’s ecosufism theory and combining it with ecological principles. It can be one of the effective ways to offer a sustainable ecological management model that can be widely adopted to overcome environmental problems that modern humans face today.